Simulation of fast recursive least square algorithm for echo cancellation system - Kamaruddin, Rosita (2003)
There are numerous techniques utilized for echo cancellation. The current trend is using digital signal processing techniques. Currently, adaptive filtering methods are extensively used in echo cancellation. The performance of echo canceller depends on the choice of the adaptive filtering using Fast Recursive Least Square (FRLS) algorithm. This thesis described the performance of Fast Recursive Least Square (FRLS) algorithm for transversal filter and recursive filter for echo cancellation system in a typical telephone network. The performance of FRLS algorithm for both filters is described and evaluated by using MATLAB software .. The results produced by the simulation process were analyzed in terms of convergence rate and complexity of the algorithm for echo cancellation system. It also looked how the number of taps and iteration influences the result of simulation. The results indicated good agreement with theoretical result. It also proves that the algorithm can be used and capable for echo cancellation purpose.